Relationship of Food Variations, Snack Food, and Physical Activities with the Nutrition Status of Students in Labuhan Batu District - Harahap, Nova Lila; Lestari, Wanda; Manggabarani, Saskiyanto (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
Background: One group of school-age children has nutritional problems. The problem of excess nutrients can affect body function, while a nutrient deficiency can cause impaired body growth and maturity of the reproductive organ system. Also, daily nutritional deficiencies can cause a lack of concentration in learning. Purpose: To determine the effect of food consumption patterns on nutritional status. Method: The research design used was observational with a cross-sectional study approach. This research was conducted at SMP Negeri 3 Satu Atap Batu Bujur, West Bilah Subdistrict, Labuhan Batu Regency, North Sumatra Province with a research sample of 78 students consisting of class VII and VIII aged 13-15 years. The sampling technique in this research is using the total sampling method. Data analysis was performed univariate and bivariate using the Chi-Square test. Results: dietary variation was associated with nutritional status with a p-value (0.010). Snack food was related to nutritional status with a p-value (0.45). Physical activity is related to nutritional status with a p-value (0.030). Conclusion: There is a correlation between dietary variation, snack food, and physical activity with nutritional status among students. It is recommended that students keep their food consumption and physical activity in accordance with nutritional needs.Keywords: Food Variation, Snack Food, Physical Activity, Nutritional Status.